Perawatan Kopling Dan Instalasi Listrik Untuk Pengujian Kinerja Mesin Bensin 3K Dengan Metode Variable Speed - Maksum Ardi, Hanni; Syamsurizal, Nazmi; Munir Fahmi, Mokhamad; Setiawan, Dibyo (CV. Multi Kreasi Media, 2024)
The main issue at the Fluid Thermal and Automotive Laboratory of Bandung State Polytechnic is the malfunctioning of the Corona 3K gasoline engine used for practical activities, due to the absence of a clutch transmission and electrical installation. This research aims to recondition the engine through clutch installation and electrical wiring to support performance testing with the variable speed method. The methodology includes initial inspection of components, repair or replacement, coupling and electrical assembly, and testing. The results indicate that the engine operates properly and produces performance data including fuel flow rate, fuel power, generator output, specific fuel consumption, and brake thermal efficiency. The engine is successfully restored for laboratory use.